Systems Thinking and Practice: A Guide to Concepts, Principles and Tools for FCDO and Partners - and Woodhill, Jim; Millican, Juliet (Institute of Development Studies, 2022)
This guide is a basic reference on systems thinking and practice tailored to the context and needs of the UK Government’s Foreign, Commonwealth & Development Office (FCDO). It is an output of the FCDO Knowledge for Development Programme (K4D), which facilitated a Learning Journey on Systems Thinking and Practice with FCDO staff during 2021 and 2022. The guide offers a common language and shared framing of systems thinking for FCDO and its partners. It explores what this implies for working practices, business processes and leadership. It also offers links to additional resources and tools on systems thinking. We hope it can support systems thinking to become more commonplace within the culture and practices of FCDO and working relations with partner organisations.